Studia nad baptysteriami w Polsce x wieku I: Poznań, Ostrów Tumski - Sikorski, Dariusz Andrzej (Ecclesia. Studia z Dziejów Wielkopolski, 2018)
The author presents the circumstances of the rise and development of the conception that below the oldest cathedral church in Poznań is the site of a temporary or permanent baptistery as allegedly evidenced by a round limestone bowl. Attention is drawn to the fact that so far this conception has not been supported by analysis of the source material or a detailed study of the remains of the bowl itself or the architectural remains of the purported baptistery. The author makes a reassessment of hitherto claims and shows that the state of the source material does not allow us to uphold the hypothesis of the baptismal function of the limestone bowl from Poznań. The only hypothesis competitive to the baptismal one refers to 60 analogous objects, a majority of which are beyond doubt the remains of mechanical mortar mixers. The article shows that these examples can be treated as fully justified analogies to the bowl from Poznań. The text reviews the arguments of both sides of the dispute: the baptismal and “construction” claims. Weaknesses of the argument for the baptismal interpretation are exposed. Doubts raised by skeptics concerning the interpretation of the bowl as a mortar mixer are dispelled on the basis of analysis of analogous objects. The author concludes that the interpretation of the bowl as a mortar mixer is supported by numerous analogies whereas the baptismal conception lacks such support.